The effect of compensation on employee performance through involvement and job satisfaction at PT. Wijaya Karya Serang Panimbang - Juliansyah, Iwan; Yusnita, Nancy (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
This study aims to analyze the effect of compensation on employee performance, with involvement and job satisfaction serving as intervening variables at PT. Wijaya Karya Serang Panimbang. The research is grounded in the premise that fair and transparent compensation systems play a pivotal role in fostering employees’ sense of belonging, engagement, and satisfaction, which ultimately influence overall performance outcomes. Employing a quantitative explanatory approach, the study collected primary data through a structured questionnaire distributed to company employees across operational and administrative divisions. The sampling technique used was proportional stratified random sampling, resulting in a total of 120 valid responses. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the study variables. The results indicate that compensation has a significant positive effect on employee involvement and job satisfaction, both of which, in turn, have a substantial impact on employee performance. Moreover, the mediating analysis reveals that involvement and job satisfaction partially mediate the relationship between compensation and performance, suggesting that financial and non-financial rewards enhance employees’ intrinsic motivation and engagement in their roles. The findings highlight that an equitable compensation structure, coupled with a supportive organizational climate, contributes to higher productivity and commitment. The study offers theoretical contributions to human resource management literature and practical implications for developing performance-based compensation systems that sustain workforce motivation and organizational effectiveness.